Prinsip Perlindungan yang Sama dalam Pemberian Bantuan Hukum Terhadap Pelaku Tindak Pidana Berat - Fandy Prabowo (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2018)
The legal assistance provided to the suspect or the defendant is essentially a defense of the law and the protection provided to the suspect or the defendant to be protected by rights. Often, abandonment and abuses in practice when a suspect is arrested and interrogated, an investigator rarely informs him of the right to legal aid. Whereas this provision has been regulated in Article 114 of the Criminal Procedure Code. This paper concludes with three conclusions. First, the constitution guarantees the right of every citizen to the equitable recognition, guarantee, protection and legal certainty and equal treatment before the law, including the right to access justice through the provision of legal assistance. Second, Some forms of legal guarantees against the perpetrators of serious criminal offenses who are provided with legal assistance, among others, accompanied by legal counsel provided by the state through legal aid providers that have been registered with the Ministry of Justice and Human Rights of the Republic of Indonesia. Third, there have been many judicial decisions which have had permanent legal force and become jurisprudence which contains the unauthorized report of the hearing if the suspect's rights are not submitted / met by the investigator, especially the rights related to legal aid.